(NuPOTREBLENIE PADEVEJ W RE^I (B/s - (NaRKADXEWA(B, (NoLXGA mIHAJLOWNAs ((NmOSKWA (B:s (Nmgu(B,s, 1975)
(NsPISOK LIT(B.: (NS(B. 113 - 124(233 (NNAZW(B.)s
Keywords: (NpADEVI W RUSSKOM QZYKEs; (NrUSSKIJ QZYKs